Variant SARS-CoV-2 mRNA vaccines confer broad neutralization as primary or booster series in mice. Issue 51 (17th December 2021) - Wu, Kai; Choi, Angela; Koch, Matthew; Elbashir, Sayda; Ma, LingZhi; Lee, Diana; Woods, Angela; Henry, Carole; Palandjian, Charis; Hill, Anna; Jani, Hardik; Quinones, Julian; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of a global pandemic. Safe and effective COVID-19 vaccines are now available, including mRNA-1273, which has shown 94% efficacy in prevention of symptomatic COVID-19 disease. However, the emergence of SARS-CoV-2 variants has led to concerns of viral escape from vaccine-induced immunity. Several variants have shown decreased susceptibility to neutralization by vaccine-induced immunity, most notably B.1.351 (Beta), although the overall impact on vaccine efficacy remains to be determined. Here, we present the initial evaluation in mice of 2 updated mRNA vaccines designed to target SARS-CoV-2 variants: (1) monovalent mRNA-1273.351 encodes for the spike protein found in B.1.351 and (2) mRNA-1273.211 comprising a 1:1 mix of mRNA-1273 and mRNA-1273.351. Both vaccines were evaluated as a 2-dose primary series in mice; mRNA-1273.351 was also evaluated as a booster dose in animals previously vaccinated with mRNA-1273. The results demonstrated that a primary vaccination series of mRNA-1273.351 was effective at increasing neutralizing antibody titers against B.1.351, while mRNA-1273.211 was effective at providing broad cross-variant neutralization. A third (booster) dose of mRNA-1273.351 significantly increased both wild-type and B.1.351-specific neutralization titers. Both mRNA-1273.351 and mRNA-1273.211 are being evaluated in pre-clinical challenge and clinical studies.